2005
DOI: 10.1523/jneurosci.2315-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human Anterior Cingulate Cortex Neurons Encode Cognitive and Emotional Demands

Abstract: The cortical mechanisms and substrates of cognitive and emotional demands are poorly understood. Lesion studies and functional imaging implicate the anterior cingulate cortex (ACC). The caudal ACC (cACC) has been implicated in cognitive processes such as attention, salience, interference, and response competition, mostly on the basis of neuroimaging results. To test the hypothesis that individual cACC neurons subserve these functions, we monitored neuronal activity from single cells in the cACC while subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
120
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(129 citation statements)
references
References 20 publications
7
120
0
2
Order By: Relevance
“…Taken together, our results do not support the suggested dichotomy within ACC for the attentional control of emotional relative to neutral interference. As such they are in line with some other recent reports indicating dACC rather than rACC activity in response to emotional distracters Davis et al, 2005;Haas et al, 2006;Mitchell et al, 2007). The study by Davis et al (2005) is particularly noteworthy as it involved single cell recording in humans in a region of ACC proximal to that implicated in the current study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Taken together, our results do not support the suggested dichotomy within ACC for the attentional control of emotional relative to neutral interference. As such they are in line with some other recent reports indicating dACC rather than rACC activity in response to emotional distracters Davis et al, 2005;Haas et al, 2006;Mitchell et al, 2007). The study by Davis et al (2005) is particularly noteworthy as it involved single cell recording in humans in a region of ACC proximal to that implicated in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, attentional control of nonemotional distracters is thought to implicate dACC Carter et al 1995Carter et al , 2000Durston et al, 2002;MacDonald et al 2000;Menon et al, 2001). However, some studies report dACC rather than rACC activity in response to emotional distracters Davis et al, 2005;Haas et al, 2006;Mitchell et al, 2007). Moreover, work has shown that rACC shows increased responding to emotional stimuli even in contexts where attentional control is not required Kosson et al, 2006;Pissiota et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The "cognitive" cdACC has been previously implicated in demanding tasks that involve stimulus-response selection in the face of competing streams of information including Strooplike tasks (Bush et al, 2000), and particularly in conflict resolution (Carter et al, 1998), encompassing emotionally valenced tasks (Davis et al, 2005). The second correlation may therefore be consistent with the demanding cognitive processes that demarcate drug cues as negatively valenced for drug addicted individuals (e.g., overcoming the emotional load of drug words in order to assign what is perceived to be the subjectively appropriate or socially sanctioned negative valence).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of human neuronal recording studies have been carried out in temporal (Ojemann & Schoenfield-McNeill, 1999), ventral prefrontal (Kawasaki et al, 2001) and cingulate cortex (Hutchison et al, 1999;Davis, et al, 2005). The few recordings of human MI support the existence of movement-related activity in this area (Goldring & Ratcheson, 1971;Kennedy et al, 1998), but the behavioral correlates of neurons in human frontal cortex have not been examined.…”
Section: Introductionmentioning
confidence: 99%